POTENSI MAKROFAUNA TANAH SEBAGAI BIOINDIKATOR KUALITAS TANAH GAMBUT - Eni Maftu'ah; M Alwi; Mahrita Willis (Bioscientiae, 2005)
Peat land has high potency to develop as agriculture land. It is widely distribute in Kalimantan, Sumatera, Sulawesi and Irian Jaya.  One of constrains in peat land is low in fertility due to low of soil quality. Soil quality of peat land depends on peat decomposition rate and depth of peat. Soil macrofauna has a role in decomposition, carbon cycle, nutrient redistribution and soil aggregation. To become bioindicator of soil quality, soil macrofauna should have some characteristics such as specific response, sensitive to conditional change and abundantly found. The study conducted on distinct land use in Basarang and Kalampang, Central Kalimantan. Samples of soil macrofauna collected by using hand sortir and pit fall trap methods on rainy season and dry season in 2004.  Result of the study  showed that different of land use correlated to population and diversity of soil macrofauna. Diversity of epigeic macrofauna significantly correlated with C-organic and C/N ratio, while diversity of endogeic macrofauna correlated to pH, C-organic and soil water content. Earthworm, ant, and millipida are soil macrofauna that have a potency as bioindicator of peat soil.